(untitled) (Ameghiniana, 2017)
Large archosaurs from the early part of the archosaur radiation are exceedingly rare and with few exceptions, most of these remains consist of fragmentary postcrania. We redescribe the fragmentary skull of Luperosuchus fractus from the early Middle–Late Triassic Chañares Formation of Argentina, assign newly discovered fragments from the original excavation to the same individual, and analyze its phylogenetic affinities. The dorsally convex and mediolaterally compressed anterior portion of the nasal (= ‘Roman-nose’), convex and circular knob on the dorsolateral margin of the postorbital, and a long anterior process of the prefrontal that fails to extend to the anterior end of the frontal are considered autapomorphies of Luperosuchus. The elongated gap between the nasal and maxilla is likely an artifact of preservation and this prompted a critical reevaluation of the supposed openings in the anterior portion of the skull of other suchians. We confirm that Luperosuchus is a loricatan (composed mostly of the taxa classically termed as ‘rauisuchians’) using a well sampled phylogeny and find a close relationship with the other large southwestern Pangean forms, Prestosuchus chiniquensis and Saurosuchus galilei. We also show that the holotype of Luperosuchus is the only known specimen of the taxon and all other previously referred material cannot be assigned with confidence to it. Resumen. OSTEOLOGÍA Y RELACIONES FILOGENÉTICAS DE LUPEROSUCHUS FRACTUS (ARCHOSAURIA: LORICATA) DEL TRIÁSICO TARDÍO MEDIO O TEMPRANO TARDÍO DE ARGENTINA. Los grandes arcosaurios del comienzo de la radiación de este grupo son excesivamente raros salvo algunas excepciones, la mayoría de los restos consisten en fragmentos postcraneanos. Describimos el cráneo fragmentario de Luperosuchus fractus del Triásico temprano Medio–Tardío de la Formación Chañares de Argentina, asignamos nuevos fragmentos descubiertos de la excavación original del mismo individuo, y analizamos sus afinidades filogenéticas. La parte anterior dorsalmente convexa y mediolateralmente comprimida del nasal (= nariz romana), la protuberancia convexa y circular en el margen dorsolateral del postorbital, y un proceso anterior largo del prefrontal que no logra extenderse hasta el extremo anterior del frontal son considerados autapomorfías de Luperosuchus. El largo espacio entr el nasal y el maxilar es probablemente un artefacto preservacional y sugeriría una reevaluación crítica de las supuestas aberturas de la parte anterior del cráneo de otros suquios. Confirmamos que Luperosuchus es un loricata (compuesto mayormente por los clásicos nombrados “rauisuchians”), usamos un muestreo filogenético amplio y encontramos una relación más cercana con otras formas del sudoeste de Pangea, Prestosuchus chiniquensis y Saurosuchus galilei. También demostramos que el holotipo de Luperosuchus es el único espécimen conocido y todos los otros materiales referidos no pueden asignarse con certeza.